Taking and Making Notes for Knowledge: Elevating Junior High Students’ Reading Comprehension - Rani Rizqi Ambarwati; Ruslin Ruslin; Zulfikri Zulfikri; Afifah Afifah (Faculty of Education and Teacher Training of UIN Palopo, 2025)
Reading comprehension remains a persistent challenge for many EFL learners, especially at the junior high school level, where students often struggle to actively engage with texts. This study, however, examined the effectiveness of the Taking and Making Notes (TMN) technique in improving reading comprehension in these situations. This study used a quantitative quasi-experimental design with 64 eighth-grade students at SMPN 1 Palu involving two parallel classes. The experimental class was taught using the TMN technique, while the control class was taught using the conventional method. Data were obtained through pre- and post-tests, consisting of 20 multiple-choice questions and essays. SPSS version 31 was used to conduct statistical analysis, including descriptive statistics, normality and homogeneity tests, Independent and Paired Samples t-tests. The results showed that the experimental class achieved a significant increase in the mean score from 49.06 during the pre-test to 80.78 during the post-test; meanwhile, the control class's score only increased from 53.75 to 66.56. By increasing students' active engagement, improving retention, and enhancing their thinking skills, the independent samples t-test showed a statistically significant difference between the two groups (p < 0.05), indicating that TMN can be a useful method for improving students' reading comprehension.